Seditious allegories : John Thelwall & Jacobin writing - Scrivener, Michael Henry, 1948- (University Park, Pa. : Pennsylvania State University Press, 2001)
The multifaceted career of John Thelwall (1764-1834)-poet, novelist, playwright, journalist, politician, scientist-is the lens through which we are offered here a new look at the phenomenon of British Jacobinism, long distorted by the critical view of it as intellectually weak bequeathed to us by Coleridge and Wordsworth, once Jacobins themselves. This book, the first on Thelwall in almost one hundred years, combines literary analysis and historical description to show how this innovative political activist remained true to his radicalism while adapting his methods in the face of the anti-Jacobin reaction that Paine's The Rights of Man helped set off. The three parts of the book set Thelwall's achievements and challenges in the political and literary context of his times. Part One, "Jacobin(s) Writing," focuses on the most essential aspects, ideologically and formally, of the insurgent writing of the 1790s to which Thelwall contributed. Part Two, "The Voice of the People," treats both Thelwall's radical oratory and journalism, as well as his writings and activities as a natural scientist and rhetorician, a professor and technician of "elocution." Part Three, "Jacobin Allegory," expounds on Thelwall's characteristic strategy of indirect expression through synecdoche and allegory, which he used in his later career after repression forced him out of politics. Through Thelwall's life Michael Scrivener succeeds in revealing how British Jacobinism reshaped the public sphere, initiating numerous literary experiments with oratory, pamphlets, periodicals, popularizations, and songs in the spaces opened up by political associations, lectures, meetings, and trials. Jacobinism thus altered the very institutions of reading and writing by expanding literacy, restructuring the popular arena for reading, and generating a body of diverse texts that were "seditious allegories."
Jacobinism -- Defining Jacobinism -- Thelwall's Replies to Burke -- The Voice of the People -- Thelwall's Popular Poetry and LCS Culture -- Excursus: Radical Underground: Spence and Wedderburn -- Intemperance, Oratory, and Voicelessness -- Jacobin Allegory -- Peripatetic Imagination -- Against Empire -- Autobiographies.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Thelwall, John, -- 1764-1834 -- Political and social views; Thelwall, John, -- 1764-1834; Politics and literature -- Great Britain -- History -- 18th century; Literature and society -- Great Britain -- History -- 18th century; France -- History -- Revolution, 1789-1799 -- Influence; English literature -- French influences; Jacobins -- Great Britain -- History; Social problems in literature; Sedition -- Great Britain; Radicalism in literature; Allegory; Politique et littérature -- Grande-Bretagne -- Histoire -- 18e siècle.; Littérature et société -- Grande-Bretagne -- Histoire -- 18e siècle.; Jacobins -- Grande-Bretagne -- Histoire; Problèmes sociaux dans la littérature.; Sédition -- Grande-Bretagne.; Radicalisme dans la littérature.; Allégorie.; allegories (literary genre); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; BIOGRAPHY & AUTOBIOGRAPHY / Literary; Allegory; English literature -- French influences; Influence (Literary, artistic, etc.); Jacobins; Literature and society; Political and social views; Politics and literature; Radicalism in literature; Sedition; Social problems in literature; France; Great Britain; Jakobijnen; Politieke activiteit; Letterkunde; Engels; English Literature; English; Languages & Literatures; 1700-1799; History